Javanese Language Speech and the development of Javanese language varieties : Tracing the locus, illocutionary and Perlocution in Legi Market Ponorogo - Anis Setiyanti (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2020)
This study aims to analyse the speech of locus, illocutionary and perlocution which are found in the speeches of traders and buyers in the Legi Market in Ponorogo Regency, and the function of the use of Javanese speech acts in Legi Market , Ponorogo Regency. This study uses a descriptive qualitative method with research data sources in the form of oral speech. Data collection techniques use basic techniques and advanced techniques. The basic technique used is tapping technique and the advanced technique used is the recording technique and note taking technique. The research instruments include researchers, recording devices (mobile phones), stationery, note-taking notes and books that are relevant to research. From the results of the study, researchers obtained 25 data records. Researchers find speech acts based on speech including; speech acts locution, illocution and perlokusi. Illocutionary speech acts used in conversations of traders and buyers in the Legi Market include: speech acts reporting, urgent speech acts, speech acts suggesting, speech acts announcing. Perlokusi speech acts include: speech acts to persuade, annoying speech actions, speech acts attract attention. Illocutionary functions used in conversations of traders and buyers in the Legi Market include; assertive speech acts, commissive speech acts, directive speech acts, and expressive (evaluative) speech acts